Cognitive And Psychological Dimensions Of Colours In Mind Maps: A Case Study Of Second Year Bachelor Students At The Teachers' Training School Of Constantine - Abid Charef Mouldia; Beghoul Youcef (University of Eloued جامعة الوادي, 2025)
Mind Maps are brain-friendly creative visual tools for organizing, representing and processing information. An indispensable component in Mind Maps’ design is colours. So, this study investigates the cognitive and psychological impact of colours on second year students at the Department of English at the Teachers’ Training School in Constantine “Assia Djabar” inspecting their attitudes towards their efficiency and feasibility in the prewriting phase. On this ground, a post-attitude questionnaire was administered to a randomly chosen sample of 25 students. A quantitative method was used and the data analysis was purely descriptive. The results revealed that the participants demonstrated an inclination to use colours in their Mind Maps for enhancing their cognitive performance (memorability, attention and focus, and creativity and imagination) and improving their psychological state (motivation, interest, stress and anxiety). They also manifested their awareness about the central role of colours in their Mind Maps’ designs.
Article . Ex Professo. Vol. 10. N1 . 10/04/2025
Keywords: Mind Maps; Buzan’s Mind Maps; brain- friendly; Cognitive effects; Psychological impacts